Kajian Literatur : Pengaruh Pupuk Organik Cair terhadap Pertumbuhan dan Hasil Tanaman di Lahan Kering - Nensia Natalia Waruwu; Dede Setia Putra Gea; Octavianis Laoli; Awal Sepkurniawan Waruwu; Natalia Kristiani Lase (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2024)
The use of liquid organic fertilizer (POC) is an innovative solution to increase crop productivity in drylands that face challenges in soil fertility and water availability. This study aims to evaluate the effect of various types of POC, including moringa, kirinyu, rabbit urine, fermented fruit waste, and local microorganism-based (MOL) POC, on plant growth and yield. The method used was literature review and analysis of literature from various journals, theses, theses, and dissertations, which were analyzed descriptively and quantitatively. The results showed that all types of POC increased plant productivity with an average increase of 20-40% compared to the control, with rabbit urine recording the highest increase of 40%. The effectiveness of POC comes from the content of nutrients, bioactive compounds, and microorganisms that improve soil structure, increase water retention, and spur nutrient absorption. The discussion underscored the importance of utilizing local resources to reduce environmental pollution and improve agricultural sustainability. In conclusion, POC proved to be an effective alternative to increase crop yields in drylands while supporting sustainable agriculture. Recommendations for further research include further exploration of local organic materials and application of POC on a field scale.